A case report of right cardiac ventricle perforation by uncontrolled embolization coil inserted for treating penile veno-occlusive dysfunction - Geng-Long Hsu; Yi-Kai Chang; I-Ni Chiang; Chih-Yuan Hsu; Hong-Chiang Chang; Shih Chieh Jeff Chueh (Urology Case Reports, 2022)
Coil embolization (CE) is believed effective-safe for treating penile veno-occlusive dysfunction (VOD). From 2012 to 2016, refractory impotence prompted four men to seek further treatment, although they underwent six CEs elsewhere. Uncontrolled coils scattered along penile drainage veins including the deep dorsal veins (n = 3), periprostatic plexus (n = 1), iliac vein (n = 1), right pulmonary artery (n = 2), left pulmonary artery (n = 1), and right ventricle (n = 1). The last one occurred in a 40-year-old house builder, and the coil perforated the right ventricle wall and diaphragm 18 months later. Given no sustainable improvement, CE's safety and efficacy are unreliable for treating patients with VOD.